EXPERIENCE OF USING SIMULATOR TECHNOLOGIES IN FORMING COMPETENCIES TO FUTURE NAVIGATORS USING RADAR EQUIPMENT AND GLOBAL MARITIME DISTRESS AND SAFETY COMMUNICATION SYSTEM - РИЖКОВ, Юрій; МІТІН, Юрій; ДІДЕНКО, Олександр (Zbirnyk naukovykh prat͡s︡ʹ Nat͡s︡ionalʹnoï akademiï Derzhavnoï prykordonnoï sluzhby Ukraïny. Serii͡a︡: pedahohichni nauky, 2021)
The article presents the generalization of the experience of using simulator technologies in forming the competence to future navigators regarding the use of radar equipment and global maritime communication system in case of disasters and to ensure safety.It has been found that the amendments made by the International Maritime Organization to the International Convention on Standards of Training, Certification and Watchkeeping for Seafarers have expanded the role of simulators in assessing the relevant competencies of maritime professionals. At the same time, it should be noted that logistical support of maritime higher educational institutions lags behind the requirements of modern shipping industry, the requirements of the seafarers’ labor market, and so on. It is a systemic problem that encompasses all levels of training and skills upgrading for shipping industry professionals. To solve the problem of improving the quality of professional training it has been proposed to carry out this process taking into account the principles of contextual approach, providing for the use of modern equipment and simulators, which departments and laboratories of maritime higher education institutions are equipped with. Training on simulators occupies a special place in the training of navigators, because it allows to exercise modeling of situations, which reproduce the conditions as close as possible to the real world. It is also important to include into the content of academic disciplines some components of simulator training on the formation and development of skills to work with electronic mapping systems, radio and electro-navigation equipment of ships, as well as skills associated with maritime safety (operation of fire-fighting equipment, rescue equipment, first aid on board ship, cargo operations with heavy cargo and containers, etc.). Each of these courses is taught in specialized laboratories equipped with the necessary simulation equipment in accordance with international requirements for training maritime professionals and the requirements of employers.